TRANSFORMATION OF PESANTREN ECONOMIC MANAGEMENT TOWARD SELF-RELIANCE BASED ON LOCAL WISDOM - Syaiful Anam; Ainol Yaqin; Moh Alpa Hosim (Profit: Jurnal Kajian Ekonomi dan Perbankan Syariah)
Islamic boarding schools (pesantren) play a strategic role not only as centers for education and da'wah but also as key drivers of community economic development. However, many pesantren still rely heavily on donations and external subsidies, which hinders the achievement of true financial independence. This study aims to analyze the transformation of pesantren economic management toward self-reliance based on local wisdom, with a case study on the Badan Usaha Milik Pesantren (BUMPES) Nurul Jadid.